ShadeMotion: Analyse von Baumschattenmustern - Somarriba, Eduardo; Zamora, Randall; Barrantes, José; Malek, Matthias; Vargas, Eduardo; Sinclair, Fergus; Quesada, Francisco (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2022)
Este documento está escrito en español, inglés, chino, portuguez y francés.